Pengembangan WBTB (Warisan Budaya Tak Benda) di Kota Semarang - Rozinda, Ellen Icha; Hardiyati, Zulfa Putri; Dewi, Santy Paulla (Badan Riset dan Inovasi Daerah Kota Semarang, 2022)
The development of an inclusive city in Semarang City can be supported by the development of tourism based on Intangible Cultural Heritage. Therefore, this study aims to find out what intangible cultural heritages that exist in the city of Semarang. Which of them have the potential to be developed, and analyze the prioritized development strategies. This research method is quantitative with the stages of identification of the intangible cultural heritages, determining the priority of intangible cultural heritage 1 and intangible cultural heritage 2, and determining the strategy for the development of them. The results of the study showed that the largest percentage of types of intangible cultural heritages was traditional knowledge with a value of 42%. The types of intangible cultural heritages with the smallest percentage are manuscripts, customs, and traditional sports with a value of 1%, respectively. After going through twice prioritization of the intangible cultural heritages, three of it were selected with the greatest potential for development: Warak Ngendog in Central Semarang District, Wayang Orang Ngesti Pandowo in Candisari District, and Haul KRT Sumodiningrat in South Semarang District. The SWOT strategy analysis shows that the three selected intangible cultural heritages need to be developed by improving the quality of their cultural tourism by empowering the community, providing outreach to the community to maintain cultural tourism supporting facilities and infrastructure, building tourism supporting infrastructure, and increasing stakeholder cooperation. The results of this research can contribute to help Semarang City become an inclusive city supported by Intangible Cultural Heritage-based tourism development.